Relação entre macrofauna, agregação e atributos edáficos em sequência de culturas sob plantio direto - Batista, Itaynara [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The no-tillage system (NT) is presented as an agricultural technique that improves the chemical, physical and biological soil properties. However, many questions still remain as to the effect of the type and sequence of cultures on plantsoil- organisms interactions. The objective of this study was to investigate the effect of crop sequences in no-tillage system in the community of soil macrofauna and chemical and physical characteristics of aggregates in two evaluation periods, dry and wet in areas of morphological domain of Atlantic Forest. The hypotheses tested were: e) crop rotation with species of grass/legumes (corn/soybean) favors the formation of aggregates of different morphological types with different physical and chemical characteristics, due to the action of roots and food selection by soil macrofauna; ii) the evaluation period promotes changes in the environment for the formation of aggregates due to the recent culture and seasonality; iii) biological agents (macrofauna and roots) alter the dynamics of organic matter associated with soil aggregates due to food selection by macrofauna and action of roots; iv) the rotation of grass/legumes promotes greater richness of individuals, uniformity of soil macrofauna, greater abundance of groups decomposers of organic matter and engineers of the ecosystem when compared to grasses or legumes, due to improvement in the availability of food resources. The experiment was conducted under NT in Jaboticabal - SP, the treatments analyzed were: soybean monoculture (legume) in the summer and sun hemp (legume) in the off season (S-SH), corn monoculture (grass) in the summer and corn in the off season (C-C), rotation soybean/corn in the summer and a corn in the off season (S/C-C) and rotation soybean/corn in the summer and sun hemp in the off-season (S/C-SH). The sampling was carried out in August 2012 and March 2013. ...

O sistema de plantio direto (PD) é apresentado como técnica agrícola que melhora as propriedades químicas, físicas e biológicas do solo. No entanto, ainda permanecem muitas questões quanto ao efeito do tipo e sequência de culturas sobre as interações planta-organismos-solo. O objetivo deste estudo foi investigar o efeito de sequências de culturas em sistema de plantio direto na comunidade da macrofauna edáfica e nas características químicas e físicas dos agregados em duas épocas de avaliação, seca e chuvosa em áreas de domínio morfológico de Mata Atlântica. As hipóteses testadas foram: i) a rotação de culturas com espécies de gramíneas/leguminosas (milho/soja) favorece a formação dos agregados de diferentes tipos morfológicos com diferentes características físicas e químicas, devido à atuação de raízes e a seleção alimentar pela macrofauna do solo; ii) a época de avaliação promove mudanças no ambiente para a formação dos agregados em função da cultura recente e da sazonalidade; iii) os agentes biológicos (macrofauna e raízes) alteram a dinâmica da matéria orgânica associada aos agregados do solo, devido à seleção alimentar pela macrofauna e pela atuação de raízes; iv) a rotação de gramíneas/leguminosas promove maior riqueza de indivíduos, uniformidade da macrofauna edáfica, maior abundância de grupos decompositores de matéria orgânica e engenheiros do ecossistema quando comparada com gramíneas ou com leguminosas, devido a melhoria na disponibilidade de recursos alimentares. O experimento foi realizado sob PD em Jaboticabal - SP, os tratamentos analisados foram: monocultura de soja (leguminosa) no verão e crotalária (leguminosa) na entressafra (S-C), monocultura de milho (gramínea) no verão e milho na entressafra (M-M), rotação soja/milho no verão e uma milho na entressafra (S/M-M) e rotação soja/milho no verão e crotalária ...
Relationship among macrofauna, aggregation and edaphic attributes in crop sequence under no-tillage
Keywords: Plantio direto; Matéria orgânica; Solos - Conservação; Fauna do solo; Soil fauna